2021
DOI: 10.1128/mbio.03100-20
|View full text |Cite
|
Sign up to set email alerts
|

Direct Intracellular Visualization of Ebola Virus-Receptor Interaction by In Situ Proximity Ligation

Abstract: Ebola virus (EBOV) entry into host cells comprises stepwise and extensive interactions of the sole viral surface glycoprotein (GP) with multiple host factors. During the intricate process, following virus uptake and trafficking to late endosomal/lysosomal compartments, GP is proteolytically processed to cleaved GP (GPCL) by the endosomal proteases cathepsin B and L, unmasking GP’s receptor-binding site. Engagement of GPCL with the universal filoviral intracellular receptor Niemann-Pick C1 (NPC1) eventually cul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…One of the most striking and widely reported phenotypes associated with the A82V mutation is increased resistance to the small-molecule viral inhibitor 3.47, which targets the GP-NPC1 interaction ( 12 , 22 , 23 ). We observed that the polymorphisms at positions 82 and 544 made independent and additive contributions to viral sensitivity to 3.47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most striking and widely reported phenotypes associated with the A82V mutation is increased resistance to the small-molecule viral inhibitor 3.47, which targets the GP-NPC1 interaction ( 12 , 22 , 23 ). We observed that the polymorphisms at positions 82 and 544 made independent and additive contributions to viral sensitivity to 3.47.…”
Section: Resultsmentioning
confidence: 99%
“…Because CatL can support EBOV GP-dependent entry ( 13 , 14 , 29 ), we next sought to investigate the effect of the position 82/544 polymorphisms on viral entry under CatL-limited conditions. To overcome the challenges associated with selective inhibition of CatL in cells with irreversible activity-based inhibitors, we previously generated U2OS CatL knockout (KO) cells through CRISPR/Cas9 genome engineering ( 23 ). We then tested the kinetics of lipid mixing of the GP Mayinga variants that displayed the greatest difference on wild-type (WT) U2OS cells.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate if these explants serve as robust multicellular intermediate model systems that offer insight into small molecule efficacy in a readily accessible human tissue, we assessed several well-established EBOV inhibitors for their ability to block EBOV or rVSV/EBOV GP infection in skin explants. The cysteine protease inhibitor E64, the endosomal Ca2 + channel blocking agent tetrandrine, and the pro-inflammatory cytokine interferon-γ (IFN-γ) were evaluated as they have been shown previously to block infection (16,20,45). Skin explants were submerged in media containing the appropriate concentration of inhibitor overnight at 37°C to allow tissue penetration.…”
Section: Human Skin Explants Are Effective Multicellular Model System...mentioning
confidence: 99%
“…Simple receptor-triggered fusion events occur at neutral pH leading to virus entry through the plasma membrane. Low pH-requiring class I fusion proteins from the arenavirus ( 10 , 42 , 43 ), filovirus ( 44 46 ) and arterivirus ( 47 ) families engage endosomal receptors. For Lassa fever virus (LASV), the endosomal receptor, Lamp1, is not absolutely required but rather upwardly shifts the fusion pH threshold (from ~5.0 to ~5.5), thereby enhancing infection ( 48 ).…”
Section: Sites Of Enveloped Virus Fusionmentioning
confidence: 99%